The Effect of Audit Fee, Audit Rotation, Audit Committee and Kap Size on Audit Quality (Empirical Study on Infrastructure Sector Companies Listed on the BEI in the Period of 2019-2023) - Tyara Yovanka; Diah Iskandar (Countable (Contemporary Business and Sustainability Science), 2025)
This research uses secondary data which aims to test and obtain empirical evidence regarding the influence of audit fees, audit rotation, audit committee and KAP size on audit quality. The population in this study are infrastructure companies listed on the Indonesia Stock Exchange for the period 2019-2023. The sampling technique used in this study is the purposive sampling method, with the criteria of infrastructure companies listed on the Indonesia Stock Exchange from 2019-2023, publishing complete audited annual reports from 2019-2023 and having complete audit fee data from 2019-2023, resulting in a sample of 24 companies over a period of 5 years, with a total of 120 data samples that meet the criteria. This study sample uses a logistic regression test using SPSS 25 software. The results of this study indicate that Audit Fees have a negative effect on Audit Quality, Audit Rotation does not affect Audit Quality, Audit Committees have a positive effect on Audit Quality and KAP Size has a positive effect on Audit Quality.